2005
DOI: 10.1210/me.2004-0475
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Mediates Activin-Induced Transcription of Follicle-Stimulating Hormone β-Subunit Gene

Abstract: Synthesis of FSH by the anterior pituitary is regulated by activin, a member of the FSH(beta) superfamily of ligands. Activin signals through a pathway that involves the activation of the transcriptional coregulators Smad2 and Smad3. Previous work from our laboratory demonstrated that Smad3, and not Smad2, is sufficient for stimulation of the rat FSH(beta) promoter in a pituitary-derived cell line L(beta)T2. Here, we used RNA interference technology to independently decrease the expression of Smad proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 44 publications
0
57
2
Order By: Relevance
“…Activin A stimulates the rapid phosphorylation and nuclear translocation of the R-Smads, Smad2 and Smad3 (Bernard 2004, Suszko et al 2005. These proteins partner with the co-SMAD, SMAD4, to form complexes that can bind to a palindromic SBE in the proximal promoter at 266/ 259.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activin A stimulates the rapid phosphorylation and nuclear translocation of the R-Smads, Smad2 and Smad3 (Bernard 2004, Suszko et al 2005. These proteins partner with the co-SMAD, SMAD4, to form complexes that can bind to a palindromic SBE in the proximal promoter at 266/ 259.…”
Section: Discussionmentioning
confidence: 99%
“…For example, depletion of Smad2 or Smad3 protein levels by RNAi attenuates but does not completely block effects of 24 h activin A on Fshb transcription (Fig. 2) (Bernard 2004, Suszko et al 2005. Also, mutation of the SBE in the mouse promoter abrogates the effects of over-expressed SMADs and 4 h activin A, but 24 h activin A can still significantly stimulate transcription (Fig.…”
Section: Acute Versus Chronic Regulation Of Fshb Transcription By Actmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study showed that TPC expresses SMADs mRNA and that RNAi targeting TGF-b1 mRNA and ActA mRNA inhibited gene expression of stimulatory SMADs, SMAD2, SMAD3, and SMAD4, thereby suggesting that both TGF-b1 and ActA modulate the expression of their mediators and generate signaling that acts cooperatively in thyroid cancer. Although SMAD2 and SMAD3 share a high percentage of homology and both are stimulated by the complex TGF-b/receptor or activin/ receptor, many in vitro studies have shown the differential participation of SMAD2 and SMAD3 in transducing the signal generated by TGF-b/activin in specific cell types (Kretschmer et al 2003, Suszko et al 2005. In SMAD knockout mice, this differential role of each stimulatory SMAD is evident by observation that gene inactivation of either SMAD2 or SMAD3 produces distinct phenotypes (Chang et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The solution structure of the Pitx2 homeodomain is the first to characterize a native K50 class homeodomain and elaborates on the specificity of this protein with its consensus DNA binding sequence (Chaney et al, 2005). Smad3/4, along with Pitx2, activate transcription of FSHβ (Suszko et al, 2005), which acts in an endocrine fashion to stimulate follicle development (Fig 2-4). While the full cooperative effects of the SMAD3/4 complex and Pitx2 are being unraveled, these advances demonstrate the structural intricacies that are maintained in the activin signaling pathway.…”
Section: Structures and Signals That Regulate Local And Endocrinementioning
confidence: 99%